The court as a site of rediscrimination - Morgan-Williams, Samatha (Courtroom ethnography, 2023)
This chapter provides an ethnographic analysis of how Travellers perceive the Courts and ‘justice’ (in the context of equality litigation), centring their experiences of discrimination and marginalisation. In presenting data on the adverse experiences of Travellers who have taken equality cases to the Irish District Court, Ireland’s lowest court level, we recognise the inability of existing desk-based research to capture emotional and memorial elements of adversarial court appearances for Irish Travellers. Speaking to existing literature promoting the importance of understanding how justice is experienced through court observation and lived experience. These observations allowed the authors to experience the Court through the eyes of Travellers, follow-up interviews provided insight into individual experiences which would not be accessible via observation. Ultimately, this discussion feeds into the need for a broader recognition and understanding of vulnerable court-users experiences to adequately inform reform of equality adjudication bodies, enhance judicial training, and enable actions ensuring access to justice for the most vulnerable.